(untitled) (Medico Legal Update, 2020)
Background/Objectives: This study seeks to identify correlations among critical thinking, perception of others and communication competencyamong nursing school students Method/Statistical Analysis: Survey respondents were 1st, 2nd, 3rd and 4th year students majoring in nursing at three universities of Chung Nam and Chung Buk who understood the objectives of the study and who gave their consent on participation. Findings: The critical thinking of subjects scored 3.27(1 5), their perception of others scored 3.35(1 5), empathy scored 3.15(1 5) and communication skills was 3.34(1 5). Variables affecting respondents’ communication competencywere critical thinking disposition 27.5%(?=.42, p<.001), peer relationships 7.8%(?=.27, p<.001) and perception of others 6.2%(?=.27, p<.001) with a total explanatory power of 41.5%.The study found out that, among those independent variables, critical thinking dispositionhas the greatest effect on communication competency. Improvements/Applications: Based on these findings, it seems necessary to develop curriculums and programs that include strategies for smooth communication competency and improved critical thinking among nursing school students.